LITERASI NUMERASI DALAM KURIKULUM MERDEKA: ANALISIS TEORETIS DAN PRAKTIS DI SEKOLAH DASAR - Yeni Lisdiana Dewi; Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Numeracy literacy is a fundamental competency within the Merdeka Curriculum, aimed at fostering logical, critical, and reflective thinking skills from the elementary school level. This study seeks to analyze the theoretical foundations and practical implementation of numeracy literacy in the context of Merdeka Curriculum policies at the primary education level. The research method involves a literature review of cognitive theory (Jean Piaget), constructivist theory (Lev Vygotsky), and transformative theory (Jack Mezirow), as well as a systematic review of national and international research published between 2021 and 2025. The findings reveal that strengthening numeracy literacy requires the integration of innovative learning approaches such as Realistic Mathematics Education (RME), Problem-Based Learning (PBL), and contextual thematic learning. The Minimum Competency Assessment (AKM) policy emphasizes the teacher's role in designing adaptive numeracy strategies and diagnostic-oriented formative assessments. The success of numeracy literacy development strongly depends on the support of the educational ecosystem, including school community participation, the cultivation of a numeracy-based culture in daily activities, and the establishment of school-based numeracy teams. This study concludes that enhancing numeracy literacy demands improved teacher competencies, the development of context-based teaching tools, and systematic collaboration between schools, educators, and the broader social environment in support of Merdeka Curriculum implementation.